2006
DOI: 10.1159/000096434
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Insulin Resistance in the Idiopathic Hirsutism

Abstract: Background: Idiopathic hirsutism (IH) is the second most common cause of hirsutism, after polycystic ovary syndrome and occurs in about 15% of hirsute women. There are not many studies showing whether patients with IH also have insulin resistance. In the present study, we aimed to investigate the insulin sensivity in IH with non-obese and changing hormone levels during the hyperinsulinemic-euglycemic clamp. Methods: Twenty (20) non-obese women with IH (Group I) ranging in age from 20 to 30 (mean 25 ± 5) years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…There is limited data from studies, with small sample size, on the association between IH and IR, and the results are controversial [17,20,33,34]. In contrast to our study, UnlÜ hizarci et al [33] reported a higher prevalence of impaired glucose tolerance in 32 patients with IH, in comparison to the normal controls, results similar to those of three studies conducted on 16, 20, and 31 women with IH [17,18,20]. Furthermore, Paoletti et al [19] documented that antiandrogen treatment improved hyper insulinemia in 11 women with IH.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…There is limited data from studies, with small sample size, on the association between IH and IR, and the results are controversial [17,20,33,34]. In contrast to our study, UnlÜ hizarci et al [33] reported a higher prevalence of impaired glucose tolerance in 32 patients with IH, in comparison to the normal controls, results similar to those of three studies conducted on 16, 20, and 31 women with IH [17,18,20]. Furthermore, Paoletti et al [19] documented that antiandrogen treatment improved hyper insulinemia in 11 women with IH.…”
Section: Discussionsupporting
confidence: 62%
“…Apart from the different diagnostic criteria for IH and IR used, these discrepancies could be attributed to genetic factors, lifestyle characteristics, and dietary habits. Furthermore, the recruitment methods of IH subjects and controls affects on the estimates of IR prevalence; however, subjects of the above mentioned studies were recruited from clinics [17,18,20], while our subjects were enrolled during a population-based study to minimize selection bias; variation in BMI or android obesity of study participants can partly explain the controversial findings of current studies [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some previous studies, insulin resistance has been associated with idiopathic hirsutism in BMI-matched groups. [34][35][36] However, after researchers matched BMI values among subjects in another study, 37 the observed difference in insulin resistance between control subjects and women with idiopathic hirsutism disappeared. Frajndlich and colleagues recently linked insulin resistance to ovarian volume in patients with idiopathic hirsutism.…”
Section: Discussionmentioning
confidence: 95%
“…Sarac et al [21] found that insulin mediated glucose disposal was lower in normal weight women with IH than healthy control subjects.…”
Section: Discussionmentioning
confidence: 99%